Review: Penggunaan Matriks Composite Absorbable di Bidang Kedokteran Gigi - Agus Sumono; Dwi Warna Aju Fatmawati (STOMATOGNATIC - Jurnal Kedokteran Gigi, 2014)
Biomaterial is played role in development of medical equipments, prosthesis, reparation technique, tissueengineering, drug delivery and diagnostic tools. Biomaterial in mixed forms or called composite is usually used forthose applications. Based on matrix characteristic, composite is divided into two groups, absorbable and nonabsorbable.This classification is based on their ability to absorb. This study was aimed to review the use ofabsorbable composite matrix in dentistry. The absorbable composite matrix was able to improve and replaced bonetissue or craniofacial. Absorbable composite was able to prevent infection and tissue shrinkage, so it can replace theesthetic. Absorbable composite can be used in operative dentistry and prosthodontia as filling materials anddenture. It was concluded that absorbable composite matrix could be used widely in dentistry